Effectiveness of group play therapy on depression and loneliness in 7-11 years old children with post-traumatic stress disorder PTSD caused by sexual abuse in Tehran. - kianoosh Amini; Hamidtaher Neshatdoost; Mohammad ali Mazaheri; mohammad ali Nadi (Iranian Association of Health Education and Health Promotion, 2016)
Background and objective: Recent studies have shown that one of the major effects of child sexual abuse is post-traumatic stress disorder (PTSD). PTSD can be associated with depression and loneliness, which, if untreated, lead to long-term complications. The aim of this research was to study the effectiveness of group play therapy on depression and loneliness in 7-11 years old children with PTSD caused by sexual abuse in Tehran. Materials and methods: This study was a quasi-experimental with a pre-test, posttest and follow-up design using a control group that was done in 2015. 34 children with PTSD due to sexual abuse were selected through convenience sampling and were randomly assigned to experimental and control groups. The experimental group was treated in 7 sessions with each 1.5 hours by Group play therapy. Loneliness Questionnaire and Children's Depression Inventory were used to collect the data. Data were analyzed by SPSS 20 using analysis of covariance method. Results: There was significant difference between depression and loneliness in the experimental and control groups (p = 0.000, F = 10.646), (p = 0.000, F = 29.54). By eliminating the effect of pre-test in the follow-up phase, the treatment effect was maintained. Conclusion: Group play therapy can effectively reduce depression and loneliness in children with PTSD. Paper Type: Research Article.